Cushing Syndrome Induced by Methylprednisolone: A Case Study - Suresh, Aswini; Sam, Anson; P, Gayathiri; Prabhaharan, Lakshmi Priyanka; Ravichandren, Priyadharshini (Indian Journal of Pharmacy Practice)
Corticosteroids, naturally produced by the adrenal cortex or synthetically formulated, play a vital role in various medical treatments, including asthma management. They are categorized into mineralocorticoids and glucocorticoids, each serving distinct physiological functions. Glucocorticoids, such as methylprednisolone and hydrocortisone, possess potent anti-inflammatory, immunosuppressive, anti-proliferative and vasoconstrictive properties, making them essential in controlling inflammatory diseases. However, prolonged corticosteroid use can lead to Iatrogenic Cushing’s Syndrome (ICS), characterized by central obesity, moon facies, osteoporosis, hypertension, hyperglycaemia and increased infection susceptibility. This case report discusses a 34-year-old female with a history of bronchial asthma managed with long-term methylprednisolone use, presenting with acute respiratory distress, lower limb swelling, facial swelling and abdominal pain. Clinical evaluation revealed elevated cortisol levels, leucocytosis and electrolyte imbalances. Her treatment included intravenous furosemide, nebulized bronchodilators (Levo salbutamol and ipratropium bromide), corticosteroids (budesonide and hydrocortisone), antibiotics (cefoperazone-sulbactam, gentamicin, metronidazole) and supportive therapy with oxygen and anticoagulants. The synergistic effect of bronchodilators and corticosteroids in reducing airway inflammation and bronchospasms significantly improved her respiratory function. This case underscores the importance of carefully monitoring corticosteroid therapy to prevent adverse effects like ICS while effectively managing asthma exacerbations. A balanced approach in steroid administration is crucial to minimizing complications while maximizing therapeutic benefits.
Keywords: Crushing syndrome; Glucocorticoid Side Effects; Hyper cortisol; Methylprednisolone